Brain bioenergetics during resting wakefulness are related to neurobehavioral deficits in severe obstructive sleep apnea: a 31P magnetic resonance spectroscopy study. Issue 8 (1st June 2018) - D'Rozario, Angela L; Bartlett, Delwyn J; Wong, Keith K H; Sach, Toos; Yang, Qiao; Grunstein, Ronald R; Rae, Caroline D
Abstract: Study Objectives: Obstructive sleep apnea (OSA) is a well-established cause of impaired daytime functioning. However, there is a complex inter-individual variability in neurobehavioral performance in OSA patients. We previously reported compromised brain bioenergetics during apneic sleep in severe OSA. In this study, we investigate whether brain bioenergetics during resting wakefulness are related to neurobehavioral performance. Methods: Patients attended the sleep laboratory in the evening and were kept awake over-night. Repeated testing on the 10-minute psychomotor vigilance task (PVT, at 9 pm, 11 pm, 1 am, 3 am, 5 am) and 30-minute AusEd driving simulator task (9 pm and 5 am) was performed. Brain bioenergetics (inorganic phosphate/adenosine triphosphate ratio, Pi/ATP) were measured in the temporal lobe during resting wakefulness at 7 am in a 1.5T MRI scanner using phosphorus magnetic resonance spectroscopy ( 31 P MRS). Results: Fifteen males with severe OSA (age 47.7 ± 10.4 years, body mass index [BMI] 34 ± 6.6 kg/m 2, apnea hypopnea index [AHI] 79.7 ± 21.8/hour) were investigated. A higher Pi/ATP ratio in the brain (lower phosphorylation potential) was correlated with worse PVT and driving simulator performance across the testing period (PVT lapses: r = 0.632, r 2 = 0.399, p = 0.012; and AusEd braking reaction time: r = 0.609, p = 0.016). In contrast, the conventional AHI measure of disease severity was not significantly correlated with performance (PVT lapses: r = −0.084, p = 0.8; and AusEd braking reaction time: r = −0.326, p = 0.2). Conclusions: Lower phosphorylation potential was associated with worse performance. Compromised brain bioenergetics may in part underlie the neurobehavioral deficits in untreated OSA. We speculate that better brain bioenergetics may explain why some OSA patients are relatively asymptomatic compared with others.